Pengaruh Rekrutmen Dan Pengembangan Karyawan Terhadap Kinerja Karyawan Di Radio Republik Indonesia (RRI) Bengkalis - Eryana, Eryana; Indah, Anugrah (IQTISHADUNA: Jurnal Ilmiah Ekonomi Kita, 2020)
One important factor in sustaining the company’s existence in advancing quality is by way of recruitment efforts to find prospective employees who meet certain requirements so that from them the company can choose the most appropriate people to fill existing vacancies. A clean and healthy company is certainly due to good employee performance. Employee performance will improve if employees are given the training to improve abilities and also a clear career development program. This research aims to determine the effect of recruitment and career development on employee performance in the Radio Republic of Indonesia of Bengkalis. The populations in this research were all employees of the Radio Republic of Indonesia Bengkalis, amounting to 13 people. The results showed that employee recruitment and development influenced employee performance.